"No One Talked About It": Social Work Field Placements and Sexual Harassment. (2nd October 2017) - Wood, Leila; Moylan, Carrie
ABSTRACT: Increasing student safety is an important part of Title IX compliance for colleges and universities. Sexual harassment is an all too common experience for college students, although little is known about incidences in social work field placements. The extent of training and preparation received by students from social work program and field instructors is also unknown. This study explores the extent of training and knowledge about sexual harassment in social work field placements from a sample of 535 BSW and MSW students. Only 51% of social work students received training about sexual harassment, with 21% receiving training from their school's field office. Participants who had received training felt more prepared to address safety concerns in field. Implications for social work education are discussed.